Diversidade e evolução do gênero Adenomera Steindachner, 1867 (Anura, Leptodactylidae) - Cassini, Carla Santana [UNESP] (2015)
The genus Adenomera has 16 species, six of which are Atlantic Forest dwellers. The genus has a difficult taxonomy, mostly due to the high levels of intra and interspecific polymorphism. Recently, a phylogenetic analysis using samples collected through the whole geographic distribution of the genus (roughly tropical and temperate cis-Andean South America) suggested the existence of 35 candidate species; 16 of which being Atlantic Forest dwellers.The present contribution intends to test whatever the Atlantic Forest dwellers are a monophyletic unit. An integrative approach with directly observed data on morphology and bioacoustics allowed species delimitation within the Thomei and Marmorata Clades. Based on a denser sampling of phenotipic and 16S rRNA fragments, we recovered the Atlantic Forest dwellers are a monophyletic unit, with two major clades (Thomei + Marmorata) and sister to the Hylaedactyla + Martinezi clade. The additional material allowed the delimitation and redescritpion of two species previously understood as species complexes (Adenomera marmorata and A. bokermanni). Of the 16 Atlantic Forest dwellers candidate species, we could delimit only 10; seven of those assignable to previously described species